Organizational climate among employees at the Faculty of Physical Education at Tishreen University - صقر رشا (Latakia University Journal -Medical Sciences Series, 2023)
The research aimed to identify the level of organizational climate prevailing among employees in the Faculty of Physical Education at Tishreen University. It also aimed to identify differences in the level of dimensions of the organizational climate among employees in the Faculty of Physical Education according to the job title variable. The researcher used the descriptive analytical method, and the study sample consisted of 60 workers distributed among 30 educational staff members and 30 employees who were randomly selected from the research community. The researcher used a standardized questionnaire as a tool to collect her data, and she also used arithmetic averages and the T.Test as statistical methods. The results revealed that the level of organizational climate prevailing in the Faculty of Physical Education at Tishreen University is average, in addition to the absence of differences in the opinions of the sample members on the dimensions of the organizational climate.